2020
DOI: 10.1037/tra0000764
|View full text |Cite
|
Sign up to set email alerts
|

Discussing substance use with clients during the COVID-19 pandemic: A motivational interviewing approach.

Abstract: During the COVID-19 pandemic, trauma-exposed individuals may have heightened risk for substance use. Using substances to cope may contribute to the development of problematic substance use over time. It is imperative to initiate conversations about substance use with clients during this time and motivational interviewing offers an ideal framework for doing so.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…Being personally affected by COVID-19 and being concerned about child care were found to be related to increase use of alcohol and substances. Being personally affected may be symbolic of trauma, complicated grief, or represent a generalized stressor; all of which are related to alcohol and/or substance use (Berenz et al 2016 ; Bränström and Pachankis 2018 ; Hansen et al 2020 ; Hassel et al 2013 ; Lin et al 2020 ; Moller et al 2013 ; North et al 2002 ; Read et al 2014 ; Sola et al 2019 ; Sheerin et al 2016 ; Walker et al 2020 ; Williams et al 2015 ). This relationship should be examined further to determine how being affected personally, such as individually being diagnosed with COVID, being at high risk for COVID, or knowing others who are at risk or who have been diagnosed, is related to use of alcohol and substances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being personally affected by COVID-19 and being concerned about child care were found to be related to increase use of alcohol and substances. Being personally affected may be symbolic of trauma, complicated grief, or represent a generalized stressor; all of which are related to alcohol and/or substance use (Berenz et al 2016 ; Bränström and Pachankis 2018 ; Hansen et al 2020 ; Hassel et al 2013 ; Lin et al 2020 ; Moller et al 2013 ; North et al 2002 ; Read et al 2014 ; Sola et al 2019 ; Sheerin et al 2016 ; Walker et al 2020 ; Williams et al 2015 ). This relationship should be examined further to determine how being affected personally, such as individually being diagnosed with COVID, being at high risk for COVID, or knowing others who are at risk or who have been diagnosed, is related to use of alcohol and substances.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that use of substances and alcohol may represent a negative form of coping (Lagisetty et al 2017 ; Ornell et al 2020 ; Schulte and Hser 2014 ). In particular, increased alcohol and/or substance use is related to disasters (Bonanno et al 2007 ; Galea et al 2020 ), exposure to violence (Hotton et al 2019 , Rougemont-Bücking et al 2017 ), and traumatic events (Berenz et al 2016 ; Hansen et al 2020 ; Moller et al 2013 ; North et al 2002 ; Read et al 2014 ; Sheerin et al 2016 ; Walker et al 2020 ; Williams et al 2015 ). However, increased alcohol and/or substance use may only represent an acute solution and not represent a long-term coping solution (SAMSHA 2020 ).…”
mentioning
confidence: 99%
“…Recently, researchers have raised concerns that a pandemic may be a high‐risk time for heightened alcohol use (Clay and Parker, 2020; McKay and Asmundson, 2020; Walker et al, 2020; Zaami et al, 2020). On March 11, 2020, the World Health Organization declared the 2019 novel coronavirus disease (COVID‐19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) virus, to be a pandemic (Centers for Disease Control and Prevention [CDC], 2020).…”
Section: Current Studymentioning
confidence: 99%
“…Alongside the multitude of pandemic-related stressors, depression, anxiety, and loneliness increased among college students and young adults (Lee et al, 2020;Li et al, 2020). Concern was raised that, to cope with such distress, some individuals may have increased their drinking (Clay and Parker, 2020;McKay and Asmundson, 2020;Walker et al, 2020;Zaami et al, 2020), consistent with the self-medication hypothesis (Khantzian, 1985). Indeed, associations between distress and drinking to cope during the pandemic have been documented in adults in the community (Rodriguez et al, 2020;Wardell et al, 2020).…”
mentioning
confidence: 96%
“…These simulations allow individuals to gain skills and confidence around initiating and managing conversations about substance use by using evidence-based communication strategies such as motivational interviewing. Walker et al [53] points out that, in these critical times of COVID-19, MI is an ideal framework to address substance use. Even before this crisis occurred, alcohol use was the third leading cause of preventable death, and data has shown that the isolation and anxiety around the COVID-19 pandemic have increased the use of alcohol and other substances.…”
Section: Discussionmentioning
confidence: 99%